The Role of Public Libraries in Promoting Digital Literacy for Community Empowerment in Western Uganda. - Rwotolonya, Sarah Kakuru (Kabale University, 2023)
Digital literacy has become a concern in this era that is characterized by heavy dependence on the usage of Information and Communication Technologies (ICTs). To evidence this, in Uganda, 36% of the non-internet users are digitally illiterate, and the digital literacy index is still low at 20%. The aim of this study was to investigate the role of public libraries in promoting digital literacy for community empowerment in the western part of Uganda. The study was guided by the specific objectives which include; establishing the strategies undertaken by public libraries; and the challenges they encounter in promoting digital literacy for community empowerment in western Uganda. A case study design was used to gather qualitative data on the availability of library facilities, the strategies undertaken by public libraries; and assessing the challenges encountered by public libraries in promoting digital literacy for community empowerment in western Uganda. The study found out that public Libraries in Uganda are in the front line of promoting digital literacy within their communities through community outreach, face to face, and hands on training. Through these, members within the community are taught mobile phone literacy, computer skills and other life and vocation skills in liquid soap, and shoes making. These libraries also provide information and internet access in a bid to close the access gap. However, they encounter a number of challenges such as limited funding, unstable power supply, few ICT facilities, and few staff within the libraries. There is therefore a need for the government of Uganda to increase funding, recruit more staff, develop a national digital skills framework, mandate internet service providers to support public libraries with free internet access if a digital literate society is to be realised.